Electrolyte, preparation method thereof and aqueous zinc ion battery
Patent Information
- Application Number
- CN202610011072.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-06
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-01-06
AI Technical Summary
然而,锌负极在实际应用中仍面临两大挑战:锌枝晶生长和锌离子水合效应,锌枝晶是锌负极在电池循环过程中因锌离子沉积不均匀形成的针状结晶,造成活性锌的不可逆损失,还会刺穿隔膜导致电池短路或热失控;而锌离子水合效应是锌离子在水系电解液中与水分子结合形成水合壳层的现象,这会增大锌离子去溶剂化的难度,增加锌的沉积过电势并加剧副反应,并且水分子在锌负极表面的竞争吸附还会加速副反应,因此锌枝晶生长和锌离子水合效应均会降低电池的循环稳定性,但现有技术往往难以同时解决锌枝晶生长和水合效应带来的负面影响
Smart Images

Figure CN121812780B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of zinc-ion battery technology, and in particular to an electrolyte, its preparation method, and an aqueous zinc-ion battery. Background Technology
[0002] Aqueous zinc-ion batteries have shown broad application prospects in the energy storage field due to their advantages such as high safety, environmental friendliness, and low cost. However, zinc anodes still face two major challenges in practical applications: zinc dendrite growth and zinc ion hydration effect. Zinc dendrites are needle-like crystals formed on the zinc anode during battery cycling due to uneven zinc ion deposition, causing irreversible loss of active zinc and potentially puncturing the separator, leading to short circuits or thermal runaway. Zinc ion hydration effect is the phenomenon where zinc ions combine with water molecules in aqueous electrolytes to form a hydrated shell. This increases the difficulty of zinc ion desolvation, increases the zinc deposition overpotential, and exacerbates side reactions. Furthermore, the competitive adsorption of water molecules on the zinc anode surface accelerates side reactions. Therefore, both zinc dendrite growth and zinc ion hydration effect reduce the cycle stability of the battery, but current technologies often struggle to simultaneously address the negative impacts of zinc dendrite growth and hydration effects. Summary of the Invention
[0003] In view of this, embodiments of this application provide an electrolyte that, when applied to an aqueous zinc-ion battery, can reduce zinc ion hydration and deposition overpotential, promote reversible reactions, and generate a stable protective layer on the surface of the zinc anode, thereby inhibiting zinc dendrite growth and corrosion side reactions, improving the stability of the zinc anode, and thus improving the cycle stability and cycle life of the aqueous zinc-ion battery.
[0004] In a first aspect, embodiments of this application provide an electrolyte comprising a zinc salt and an electrolyte additive, wherein the electrolyte additive comprises a complex formed by an amine ligand and a reducing metal, wherein the reducing metal is less reactive than zinc.
[0005] In the embodiments of this application, the reducing metal includes one or more of chromium, cadmium, iron, cobalt, nickel, molybdenum, tin, lead, copper, mercury, and silver.
[0006] In the embodiments of this application, the amine ligands include one or more of methylamine, ethylamine, acetamide, ethylenediamine, propylenediamine, diethylenetriamine, triethylenetetramine, ethanolamine, and ethylenediaminetetraacetic acid.
[0007] In the embodiments of this application, the complexes formed by amine ligands and metal salts include one or more of ferrous ethylenediamine sulfate, triethylenediamine ferric sulfate (II), triethylenediamine cobalt sulfate, and ethylenediaminetetraacetic acid cobalt sulfate.
[0008] In the embodiments of this application, the concentration ratio of the complex formed by the zinc salt, the amine ligand and the reducing metal is 1:(0.001-0.004).
[0009] In this embodiment of the application, the concentration of zinc salt in the electrolyte is 0.5 mol / L-3 mol / L.
[0010] In the embodiments of this application, the concentration of the complex formed by the amine ligand and the reducing metal is 0.0005 mol / L-0.012 mol / L.
[0011] In the embodiments of this application, the complexes formed by zinc salts, amine ligands and reducing metals contain the same anion.
[0012] Secondly, embodiments of this application provide a method for preparing the electrolyte provided in the first aspect of this application, comprising: mixing electrolyte additives and zinc salts to obtain an electrolyte.
[0013] Thirdly, embodiments of this application provide an aqueous zinc-ion battery, including a positive electrode, a negative electrode, a separator, and the electrolyte provided in the first aspect of this application. Attached Figure Description
[0014] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. The specific embodiments described herein are merely illustrative of this application and are not intended to limit this application.
[0015] Figure 1 This is a cycle test diagram of the Zn-Zn symmetric cell of Embodiment 1 of this application; Figure 2 This is a cycle test diagram of the Zn-Zn symmetric cell of Embodiment 2 of this application; Figure 3 This is a cycle test diagram of the Zn-Zn symmetric cell of Embodiment 3 of this application; Figure 4 This is a cycle test diagram of the Zn-Zn symmetric cell of Embodiment 4 of this application; Figure 5 This is a cycle test diagram of the Zn-Zn symmetric cell of Comparative Example 1 of this application; Figure 6 These are hydrogen evolution overpotential test diagrams for Zn-Zn symmetric cells of Examples 1-4 and Comparative Example 1 of this application; Figure 7 The AC impedance test diagrams are for Zn-Zn symmetrical cells of Examples 1-4 and Comparative Example 1 of this application; Figure 8 This is a cycle performance test diagram of the Zn-I2 full cell of Embodiment 2 of this application. Detailed Implementation
[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0017] Aqueous zinc-ion batteries, with their advantages of abundant zinc resources, low cost, high safety (using aqueous electrolytes avoids the risk of combustion and explosion associated with organic electrolytes), and high theoretical specific capacity of zinc anodes, have shown broad application prospects in large-scale energy storage. However, inherent defects in zinc anodes severely restrict their performance improvement, with zinc dendrite growth and excessive zinc ion hydration being the main problems.
[0018] Zinc dendrites are formed due to the uneven deposition of zinc ions on the surface of the negative electrode. During cycling, zinc ions tend to accumulate excessively in local areas, forming needle-like or dendritic crystals. In terms of safety, zinc dendrites may penetrate the separator, causing internal short circuits, thermal runaway, and electrolyte leakage. In terms of battery performance, zinc dendrites are prone to breakage, leading to the loss of active zinc, thereby reducing the coulombic efficiency of the battery and accelerating capacity decay.
[0019] The reasons for zinc dendrite growth can be attributed to various factors, including uneven ion distribution in the electrolyte, unstable electrode interfaces, and electrochemical reactions. In addition, uneven desolvation of zinc ions is also a major cause of zinc dendrite growth. In aqueous zinc-ion batteries, zinc ions (Zn...) 2+ It is usually in the form of hydrated ions [Zn(H2O)6] 2+ Zn exists in the electrolyte in the form of [unclear - possibly a specific substance or form] during battery charging and discharging. 2+ In order to be reduced and deposited as metallic zinc on the zinc anode, a desolvation process, i.e., detachment from the water molecule shell, is required on the negative electrode surface. This ability to detach from water molecules is called the desolvation capability of zinc ions. However, this process faces the following key problem: the Zn in hydrated zinc ions... 2+ The zinc anode binds to H2O molecules through strong electrostatic forces. Desolvation requires overcoming a high energy barrier, which leads to an increase in deposition potential. This high overpotential not only reduces the energy efficiency of the zinc anode, but also, during the desolvation process, free water molecules may undergo side reactions (such as hydrogen evolution reaction) on the zinc anode surface, leading to zinc corrosion and electrolyte salt consumption, thereby affecting the reversible reaction of the battery cycle.
[0020] Existing solutions often focus on improving single problems, such as adjusting the zinc ion solvation structure through organic additives or using inorganic salt additives to form an artificial solid electrolyte interface (SEI). However, these methods often fail to simultaneously address the combined problems caused by zinc dendrites and zinc ion hydration effects. Therefore, developing electrolyte additives that can synergistically regulate zinc deposition behavior and optimize the stability of the zinc anode interface has become one of the solutions to overcome the technical bottleneck of aqueous zinc-ion batteries.
[0021] In view of this, embodiments of this application provide an electrolyte comprising a zinc salt and an electrolyte additive, wherein the electrolyte additive comprises a complex formed by an amine ligand and a reducing metal, wherein the reducing metal is less reactive than zinc. The electrolyte provided in this application includes a complex formed by amine ligands and reducing metals. The amine ligands in this complex are originally linked to reducing metal ions via coordinate bonds. When applied to the electrolyte of an aqueous zinc-ion battery, because the reducing metal is less reactive than zinc, zinc ions can replace the reducing metal ions and coordinate with the amine ligands. This competitive coordination is stronger than the binding force between water molecules and zinc ions, thus effectively reducing the hydration level of zinc ions. The displaced reducing metal ions undergo a redox reaction, forming a stable protective layer on the surface of the zinc anode. This protective layer enhances the interfacial stability of the zinc anode, thereby effectively inhibiting zinc dendrite growth. Therefore, the electrolyte provided in this application achieves the dual effects of reducing zinc ion hydration and inhibiting zinc dendrite growth, helping to suppress corrosion side reactions of the zinc anode, promoting reversible charge-discharge reactions, and thus improving the cycle stability of the battery.
[0022] In this application, the amine ligand can be one or more of monodentate amine ligands, bidentate amine ligands, polydentate amine ligands, cyclic amine ligands, and modified amine ligands. The core characteristic of amine ligands is that the nitrogen atom can provide a lone pair of electrons to form a coordinate bond with the metal ion, thereby forming a complex or compound. The number of teeth in an amine ligand refers to the number of nitrogen (N) atoms available for coordination in the ligand. A higher number of teeth indicates a stronger chelating effect between the metal and nitrogen atoms, resulting in more coordinate bonds that can be formed. Therefore, the stability of the complex formed by the amine ligand and the reducing metal is positively correlated with the number of teeth in the amine ligand.
[0023] In some embodiments of this application, monoamine ligands contain only one coordinating N atom, such as, but not limited to, methylamine (CH3NH2), ethylamine (C2H5NH2), and acetamide (CH3CONH2); diamine ligands contain two coordinating N atoms, such as, but not limited to, ethylenediamine (EDA, NH2CH2CH2NH2) and propylenediamine (NH2HC2CH2CH2NH2); polyamine ligands contain three or more coordinating N atoms, such as, but not limited to, diethylenetriamine (DETA, NH2CH2CH2NHCH2CH2NH2), triethylenetetramine (TETA), and polyethyleneimine (PEI); cyclic amine ligands have the N atom located on the ring, such as, but not limited to, piperazine (C4H2NH2NH2NH2NH2). 10 N2), 1,4,7-triazacyclononane (TACN); modified amine ligands include, but are not limited to, the aforementioned amine ligands that have been hydroxylated or carboxylated, such as ethanolamine (OHCH2CH2NH2) and ethylenediaminetetraacetic acid (EDTA). These modified groups have functions such as enhancing hydrophilicity or assisting film formation. In practical applications, amine ligands can be modified as needed.
[0024] In some embodiments of this application, the amine ligand is preferably a bidentate amine ligand, which forms a complex with the reducing metal with moderate stability, thereby preserving reactivity. This reduces the difficulty for zinc ions in the electrolyte to replace the coordination binding sites and displace the reducing metal ions, while avoiding premature decomposition of the complex due to weak stability. In addition, the coordination ratio between the bidentate amine ligand and the reducing metal ion is relatively fixed (e.g., 1 metal ion binds to 2-3 bidentate amine ligands), which facilitates the control of the concentration ratio of the complex formed by the amine ligand and the reducing metal to the electrolyte zinc salt, thereby achieving better technical effects.
[0025] In this embodiment, the reducing metal exists as a low-valence metal cation in the complex formed by the amine ligand and the reducing metal. A low-valence metal cation refers to a metal cation with a lower oxidation state or lower valence, whose oxidation state is lower than the highest oxidation state commonly found in that metal. It typically exhibits a certain reducing property. For example, the highest oxidation state of metallic iron is ferric ion (Fe3+). 3+ Therefore, ferrous ions (Fe) 2+ ) and monovalent iron ions (Fe + ( ) belongs to the low-valence state of iron ions; the highest oxidation state of metallic copper is divalent copper ions (Cu). 2+ Therefore, cuprous ions (Cu) + It belongs to the low-valence state of copper ions.
[0026] In this embodiment, the metal in the complex is in a low valence state. When it is displaced from the complex by zinc ions, the metal ions exhibit reducing properties and can undergo a redox reaction with water or oxygen in the electrolyte to generate a stable metal oxide, which serves as a surface protective layer for the zinc anode. On one hand, this protective layer improves the surface stability of the zinc anode and effectively inhibits zinc dendrite growth. On the other hand, while this metal oxide allows zinc ions to pass through, its conductivity is much lower than that of the metallic zinc anode. Therefore, this protective layer can block electron conduction on the zinc anode surface without hindering zinc ion transport, reducing the number of electrons that can participate in the hydrogen evolution reaction. This increases the overpotential of the hydrogen evolution reaction and reduces the probability of it occurring. The hydrogen evolution reaction refers to the chemical reaction in which hydrogen ions or water molecules gain electrons on the electrode surface and are reduced to generate hydrogen gas during electrochemical processes. This side reaction can accelerate electrode corrosion or dendrite growth, and the generated hydrogen gas can also increase the internal pressure of the battery, posing a safety hazard. For example, when the complex formed by the amine ligand and the reducing metal is ferrous ethylenediamine sulfate ([Fe(EDA)3]SO4), it is affected by Zn in the electrolyte. 2+ Fe replaced 2+ It can undergo a redox reaction on the surface of the zinc anode to generate ferrous hydroxide (Fe(OH)2) and iron(III) oxide (Fe3O4). Among them, Fe(OH)2 will be further oxidized to Fe3O4, and finally a stable Fe3O4 protective layer is formed on the surface of the zinc anode, which has the aforementioned beneficial effects.
[0027] In this application, the reducing metal is less reactive than zinc. Specifically, its reactivity is defined as follows: at 25°C, the reducing metal cannot displace elemental zinc from a zinc salt solution. In some embodiments of this application, the reducing metal may be, but is not limited to, one or more of chromium (Cr), cadmium (Cd), iron (Fe), cobalt (Co), nickel (Ni), molybdenum (Mo), tin (Sn), lead (Pb), copper (Cu), mercury (Hg), and silver (Ag).
[0028] This application specifies that the reducing metals are less reactive than zinc. On the one hand, metallic reactivity refers to the ability of a metallic element to lose electrons and react with other substances in a chemical reaction; the more reactive the metal, the easier it is to lose electrons. Based on the difference in reactivity between zinc and the aforementioned metals, Zn... 2+ Zn has a stronger ability to form coordinate bonds with the nitrogen atom in amine ligands, and its coordination affinity with the nitrogen atom is also stronger, driving coordination substitution in the system. The original reducing metal ion will break its coordinate bond with the nitrogen atom. 2+ It will occupy the coordination site to form Zn 2+New complexes with amine ligands are used to reduce the hydration of zinc ions, while the displaced reducing metal ions are oxidized and form a protective layer on the zinc anode. Furthermore, the reducing power of a metal is positively correlated with its reactivity; more reactive zinc has a more negative reduction potential. Therefore, in the electrolyte, zinc ions are preferentially reduced and deposited as metallic zinc at the anode, while ferrous ions are not reduced to metallic iron. This ensures the dominance of zinc deposition and avoids the deposition of Fe. 2+ With Zn 2+ Competitive deposition leads to a more complex composition of the negative electrode.
[0029] In this application, the complex formed by the amine ligand and the reducing metal includes a complex formed by the amine ligand and the reducing metal salt, wherein the reducing metal salt is composed of a low-valence metal cation and anion. In some embodiments of this application, the anion in the reducing metal salt may be, for example, but is not limited to, sulfate (SO42-). 2- ), chloride ions (Cl) - ), nitrate (NO3) - ), carbonate (CO3) 2- ), phosphate (PO4) 3- Acetate (COOH) - One or more of the following.
[0030] In the embodiments of this application, the molar ratio of the amine ligand to the reducing metal ion in the complex formed by the amine ligand and the reducing metal salt is 3:(0.5-3), for example, but not limited to 3:0.5, 3:0.8, 3:1, 3:1.2, 3:1.5, 3:1.8, 3:2, 3:2.5, and 3:3. This limitation aims to reduce the possibility of side reactions initiated by free metal ions or free ligands, and to ensure that the two function as a complex as possible. In some embodiments of this application, the molar ratio of the amine ligand to the reducing metal in the complex is 3:(0.5-2), which is more conducive to maximizing the function of the electrolyte additive and minimizing side effects. In some embodiments of this application, the complexes formed by the amine ligands and reducing metal salts include, but are not limited to, ferrous ethylenediamine sulfate ([Fe(EDA)3]SO4) and triethylenediamine cobalt sulfate (II). ([Co(EDA)3]SO4), Triethylenediamine ferric sulfate (II) ([Fe(EDA)3]SO4), Diethylenediamine copper sulfate (I), Tetraamminecopper sulfate (I) ([Cu(NH3)4]2SO4), Hexaammineferric sulfate (II) ([Fe(NH3)6]SO4), Hexaamminecobalt sulfate (II) ([Co(NH3)6]SO4), Ethylenediaminetetraacetic acid cobalt sulfate ([Co(EDTA)]SO4), Tetraethylamine ferric chloride ([Fe(C2H5NH2)4]Cl2), Tetramethylamine ferrous phosphate ([Fe(CH3NH2)4]3(PO4)2), Diethylenediamine cobalt(II) chloride ([Co(EDA)2]Cl2), Ethylenediaminetetraacetic acid ferric sulfate ([Fe(EDTA)]SO4), Tetramethylamine cobalt nitrate ([Co(CH3NH2)4)4) One or more of (NO3)2).
[0031] In this application, the zinc salt includes any zinc salt known in the art, such as, but not limited to, one or more of zinc sulfate (ZnSO4), zinc chloride (ZnCl2), zinc nitrate (Zn(NO3)2), zinc phosphate (Zn3(PO4)2), zinc acetate (Zn(COOH)2), and zinc trifluoromethanesulfonate (Zn(CF3SO3)2).
[0032] In some embodiments of this application, the complexes formed by the zinc salt, amine ligand, and reducing metal salt contain the same anion. This ensures a single type of anion in the electrolyte, simplifying the solvation structure and preventing weak interactions (such as electrostatic attraction) between other anions and zinc ions or amine ligands. This avoids competition or interference with the coordination process between zinc ions and amine ligands, while also improving the coordination efficiency between zinc ions and amine ligands and reducing the energy required for desolvation. For example, in some specific embodiments of this application, the zinc salt is zinc sulfate (ZnSO4), and the complex formed by the amine ligand and reducing metal salt is ferrous ethylenediamine sulfate ([Fe(EDA)3]SO4), both of which have sulfate (SO4) anions. 2- In other specific embodiments of this application, the zinc salt in the electrolyte is zinc chloride (ZnCl2), and the complex formed by the amine ligand and the reducing metal salt is tetraethylamine ferric chloride ([Fe(C2H5NH2)4]Cl2), both of which have chloride ions (Cl-). - ).
[0033] In the embodiments of this application, the concentration ratio of the complex formed by the zinc salt, the amine ligand and the reducing metal in the electrolyte is 1:(0.001-0.004), for example, but not limited to 1:0.001, 1:0.0015, 1:0.002, 1:0.0025, 1:0.003, 1:0.0035, 1:0.004. The complex formed by zinc salt, amine ligand, and reducing metal plays a crucial role in providing amine ligands for zinc ion coordination, thereby replacing and displacing reducing metal ions to form a protective layer on the zinc anode surface. The mechanism of this complex depends on and serves zinc ions; therefore, the concentration ratio of the complex to zinc ions is decisive for the beneficial effect of the electrolyte additive. In this application, the zinc ion content is used as a benchmark, limiting the complex concentration to 0.001-0.004 times the zinc salt concentration. This aims to ensure sufficient amine ligands and reducing metal ions are released to coordinate with zinc ions and minimize their hydration. Simultaneously, the complex concentration is avoided from exceeding the zinc ion requirement, which could lead to excessive ferrous ion oxidation and deposition, forming an overly thick protective layer that hinders zinc ion migration.
[0034] In some embodiments of this application, the concentration ratio of the complex formed by zinc salt, amine ligand, and reducing metal in the electrolyte is 1-(0.001-1:0.003). In some specific embodiments of this application, the concentration ratio of the complex formed by zinc salt, amine ligand, and reducing metal in the electrolyte is 1-(0.002-1:0.003). This concentration range has a better positive impact on the battery's performance, such as zinc deposition, hydrogen evolution overpotential, AC impedance, ion transport, and cycle life.
[0035] In this embodiment, the concentration of zinc salt in the electrolyte is 0.5 mol / L-3 mol / L, for example, but not limited to, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.8 mol / L, 2 mol / L, 2.3 mol / L, 2.5 mol / L, 2.8 mol / L, and 3 mol / L. Within this concentration range, sufficient zinc ions are provided to wet the electrodes and meet the ionic conductivity requirements of the battery, while matching the solubility of zinc salt in aqueous solvents to avoid salting out or excessively high electrolyte viscosity that hinders ion migration. In some embodiments of this application, the concentration of zinc salt in the electrolyte is 1 mol / L-3 mol / L. In some specific embodiments of this application, the concentration of zinc salt in the electrolyte is 1 mol / L-2 mol / L, a concentration range that is beneficial for further balancing ionic conductivity and electrolyte stability.
[0036] In this embodiment of the application, the concentration of the complex formed by the amine ligand and the reducing metal in the electrolyte is 0.0005 mol / L-0.012 mol / L, for example, but not limited to, 0.0005 mol / L, 0.001 mol / L, 0.002 mol / L, 0.003 mol / L, 0.004 mol / L, 0.005 mol / L, 0.006 mol / L, 0.007 mol / L, 0.008 mol / L, 0.009 mol / L, 0.01 mol / L, 0.011 mol / L, and 0.012 mol / L. The concentration of complexes formed by amine ligands and reducing metals as electrolyte additives greatly affects battery performance. Too low a concentration is insufficient to form a complete protective layer covering the zinc anode surface, nor is it sufficient to effectively destroy the hydrated shell of zinc ions, and it is even more difficult to fully realize the synergistic effect of coordination regulation and protective layer. On the other hand, too high a concentration will increase the viscosity of the electrolyte and affect battery performance.
[0037] In some embodiments of this application, the concentration of the complex formed by the amine ligand and the reducing metal in the electrolyte is 0.001 mol / L to 0.01 mol / L. In some embodiments of this application, when the concentration of zinc salt in the electrolyte is 1 mol / L to 2 mol / L, the concentration of the complex formed by the amine ligand and the reducing metal in the electrolyte is 0.002 mol / L to 0.008 mol / L. In some specific embodiments of this application, the concentration of zinc sulfate in the electrolyte is 2 mol / L, and the concentration of ferrous ethylenediamine sulfate is 0.002 mol / L to 0.006 mol / L.
[0038] In this embodiment, the pH value of the electrolyte is 3-7, for example, but not limited to 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7. A suitable pH value of the electrolyte helps to maintain the stability of the reversible reaction of the zinc anode and the stability of the cathode material.
[0039] In this embodiment, the electrolyte includes zinc salt, electrolyte additives, and solvent, and the solvent may be, but is not limited to, water.
[0040] In some embodiments of this application, the electrolyte may further include a second electrolyte additive that is different from the aforementioned electrolyte additive. The aforementioned electrolyte additive is the first electrolyte additive, and the second electrolyte additive may be, for example, but not limited to, one or more of the following: metal salt additives, small organic molecule additives, organic polymer additives, ionic liquid additives, nanomaterial additives, organic salt additives containing specific functional groups, and acid-base regulators. In some embodiments of this application, metal salt additives may include, but are not limited to, potassium sulfate, manganese sulfate, ferric sulfate, zinc fluoride, potassium hexafluorophosphate, etc.; organic small molecule additives may include, but are not limited to, dimethyl sulfoxide, N,N-dimethyl amide, trimethyl phosphate, 1,5-pentanediol, triethanolamine, sodium dodecyl sulfonate, etc.; organic polymer additives may include, but are not limited to, water-soluble chitosan, glucomannan, polyethylene glycol, polyvinyl alcohol, polyacrylamide, polyethylene oxide, etc.; ionic liquid additives may include, but are not limited to, 1-ethyl-3-methylimidazolium tetrafluoroborate, etc.; nanomaterial additives may include, but are not limited to, cellulose nanocrystals, chitin nanocrystals, carbon nanomaterials, etc.; organic salt additives containing specific functional groups may include, but are not limited to, organic salts containing functional groups such as hydroxyl, amino, carboxyl, sulfonic acid, phosphate, nitrogen-containing heterocycles, etc.; acid-base regulators may include, but are not limited to, acetic acid, sodium sulfate, phosphate buffer solutions, etc.
[0041] The electrolyte provided in this application uses zinc salt as the electrolyte salt and introduces a complex formed by amine ligands and reducing metals as an additive. Based on the difference in reactivity between the metal and zinc in the complex, zinc ions are encouraged to break free of the hydrated shell and coordinate with the amine ligands. The newly formed complex can easily perform zinc ion intercalation and deintercalation under the action of the battery electric field, thereby effectively improving the desolvation ability of zinc ions, reducing the zinc deposition overpotential, facilitating the uniform deposition of metallic zinc, and inhibiting zinc dendrite growth. At the same time, the metal ions replaced by zinc ions have reducing properties and can be oxidized on the negative electrode surface to form a stable protective layer. This protective layer can further inhibit zinc dendrite growth, and its conductivity is much lower than that of metallic zinc, thus significantly reducing electron accumulation on the zinc negative electrode surface, effectively reducing hydrogen evolution side reactions, improving interface stability, and specifically solving the problems of zinc dendrite growth and high zinc ion hydration in aqueous zinc-ion batteries. On this basis, further optimization of the number of teeth of the amine ligands has a significant promoting effect on improving the cycle stability of the battery.
[0042] As described above, the coordination reaction of zinc ions and the formation of a protective layer on the zinc anode surface by reducing metal ions have a synergistic effect on inhibiting zinc dendrite formation and reducing the hydration degree of zinc ions. Furthermore, these two processes can promote each other. Specifically, the substitution coordination reaction of zinc ions provides reducing metal ions for the formation of the protective layer. Within a suitable concentration range, the more zinc ions are coordinated and bound, the more conducive it is to accelerating the formation of a uniform and complete protective layer. Conversely, the protective layer provides active adsorption sites, stabilizes the interface pH, and improves ion transport, thus promoting the coordination reaction between zinc ions and amine ligands. This synergistic effect can further reduce the difficulty of zinc ion desolvation, inhibit hydrogen evolution and zinc dendrite growth, thereby effectively improving battery performance.
[0043] Therefore, compared to the simple combination of amine ligands and reducing metal salts, the embodiments of this application use the complex of the two as components of the electrolyte additive, which is more conducive to exerting synergistic and mutually promoting effects and optimizing the cycle stability of the battery.
[0044] This application provides a method for preparing the aforementioned electrolyte, which includes mixing electrolyte additives and zinc salts to obtain the electrolyte.
[0045] In some embodiments of this application, the preparation of the electrolyte includes adding an electrolyte additive to a zinc salt solution, stirring until homogeneous, and obtaining the electrolyte.
[0046] In this application embodiment, the stirring device includes, but is not limited to, a magnetic stirrer; the stirring speed is 1000r / min-2000r / min, for example, but not limited to 1000r / min, 1200r / min, 1500r / min, 1800r / min, 2000r / min; the stirring time is 30min-60min, for example, but not limited to 30min, 35min, 40min, 45min, 50min, 55min, 60min.
[0047] In some embodiments of this application, the preparation method of the complex formed by the amine ligand and the reducing metal includes: dissolving the reducing metal salt in deoxygenated water at room temperature (20℃-30℃), then adding the amine ligand, mixing thoroughly, adjusting the pH to 5-6, concentrating under reduced pressure, cooling to precipitate crystals, filtering and washing to obtain the complex formed by the amine ligand and the reducing metal.
[0048] In some specific embodiments of this application, the complex formed by the amine ligand and the reducing metal is ferrous ethylenediamine sulfate, which is prepared by: dissolving ferrous sulfate in deoxygenated water at room temperature (20℃-30℃) (e.g., by removing oxygen from the water by passing an inert gas through the solution), and then mixing the ferrous sulfate in a Fe molar ratio of... 2+Add ethylenediamine to EDA=1:(1-3), stir until clear, adjust pH to 5-6 (e.g., adjust pH with dilute sulfuric acid and sodium hydroxide), concentrate under reduced pressure, cool to precipitate crystals, filter and wash with ethanol to obtain ferrous ethylenediamine sulfate.
[0049] The electrolyte preparation method provided in this application embodiment only requires thorough mixing of zinc salt solution and electrolyte additive solution to obtain electrolyte. It is simple to operate and suitable for rapid preparation.
[0050] This application also provides an aqueous zinc-ion battery, including a positive electrode, a negative electrode, a separator, and the electrolyte provided above.
[0051] In some embodiments of this application, the negative electrode of the aqueous zinc-ion battery is a zinc electrode.
[0052] In some embodiments of this application, the positive electrode of the aqueous zinc-ion battery can be any positive electrode known in the art. In some embodiments of this application, the positive electrode can be a manganese-based compound electrode, a vanadium-based compound electrode, an organic positive electrode material electrode, a Prussian blue analog electrode, or a polymer material electrode. In the embodiments of this application, the positive electrode can be prepared using any method known in the art.
[0053] In some embodiments of this application, the separator of the aqueous zinc-ion battery can be any separator known to those skilled in the art, such as, but not limited to, one or more of the following: polyolefin microporous membrane, polyethylene terephthalate separator, polyethylene felt, polyvinylidene fluoride separator, nylon separator, glass fiber felt, ultrafine glass fiber paper, and composite membrane.
[0054] This application also provides an electronic device, which includes the aqueous zinc-ion battery provided above, and the aqueous zinc-ion battery powers the electronic device. In some embodiments of this application, the electronic device may be, for example, a smart wearable device, a portable sensor, a wireless mouse, a keyboard, a home energy storage device, an electronic toy, an underwater detector, a diving watch, an auxiliary power supply device, and an energy storage device.
[0055] The technical solutions of this application will be further described below with reference to several embodiments. Unless otherwise specified, the raw materials used in the embodiments of this invention are all commercially available products.
[0056] Example 1 Electrolyte preparation: A 2 mol / L zinc sulfate solution was prepared using water as the solvent. Ferrous ethylenediamine sulfate was added to the solution, and the mixture was stirred at 1000 rpm for 30 minutes using a magnetic stirrer to obtain the electrolyte. The concentration of zinc sulfate in this electrolyte was 2 mol / L, and the concentration of ferrous ethylenediamine sulfate was 0.002 mol / L.
[0057] Example 2 The only difference from Example 1 is that the concentration of ferrous ethylenediamine sulfate in the electrolyte is 0.004 mol / L.
[0058] Example 3 The only difference from Example 1 is that the concentration of ferrous ethylenediamine sulfate in the electrolyte is 0.006 mol / L.
[0059] Example 4 The only difference from Example 1 is that the concentration of ferrous ethylenediamine sulfate in the electrolyte is 0.008 mol / L.
[0060] Example 5 The only difference from Example 1 is that the concentration of ferrous ethylenediamine sulfate in the electrolyte is 0.01 mol / L.
[0061] Example 6 The only difference from Example 1 is that 0.002 mol / L ferrous ethylenediamine sulfate is replaced with 0.004 mol / L triethylenediamine cobalt sulfate (II). Comparative Example 1 The only difference from Example 1 is that the electrolyte does not contain ferrous ethylenediamine sulfate.
[0062] Comparative Example 2 The only difference from Example 1 is that 0.002 mol / L ferrous ethylenediamine sulfate is replaced with 0.004 mol / L ethylenediamine.
[0063] Comparative Example 3 The only difference from Example 1 is that 0.002 mol / L ferrous ethylenediamine sulfate is replaced with 0.004 mol / L ferrous sulfate.
[0064] Comparative Example 4 Electrolyte preparation: A 3 mol / L zinc sulfate solution was prepared using water as the solvent. Ethylenediamine and ferrous sulfate solutions were then added to the solution, and the mixture was stirred at 1000 rpm for 30 minutes using a magnetic stirrer to obtain the electrolyte. The concentrations of zinc sulfate, ethylenediamine, and ferrous sulfate in this electrolyte were 2 mol / L, 0.004 mol / L, and 0.004 mol / L, respectively.
[0065] The electrolytes from Examples 1-6 and Comparative Examples 1-4 were used to construct zinc-zinc (Zn-Zn) symmetrical cells and zinc-copper (Zn-Cu) half-cells, respectively. The specific assembly method of Zn-Zn symmetric cells: High-purity (>99.99%) zinc foil with a thickness of 0.1mm is punched using a stamping machine. Zinc discs are pressed into 12mm diameter discs. One zinc disc is placed in the negative electrode battery casing, covered with a 16mm diameter glass fiber separator, and 100uL of electrolyte is added. Another zinc disc is then placed on top of the electrolyte, and finally the positive electrode battery casing is covered. The casing is then sealed on a sealing machine to obtain a Zn-Zn symmetric battery.
[0066] The specific assembly method of Zn-Cu half cell is as follows: High-purity (>99.99%) zinc foil with a thickness of 0.1 mm is stamped into zinc discs with a diameter of 12 mm using a stamping machine. One zinc disc is placed in the negative electrode battery shell, covered with a glass fiber membrane with a diameter of 16 mm, and 100 μL of electrolyte is added. Then, a copper disc is stacked on top of the electrolyte. Finally, the positive electrode battery shell is covered, and the Zn-Cu half cell is sealed on a sealing machine to obtain the Zn-Cu half cell.
[0067] The Zn-Zn symmetric cells assembled from the electrolytes of Examples 1-6 and Comparative Examples 1-4 were subjected to cycle performance tests, hydrogen evolution overpotential tests, and AC impedance spectroscopy tests, respectively. 1) Cyclic performance testing method: Constant current charge-discharge test is performed using a battery testing system, with the current density set to 10 mA cm⁻¹. -2 The capacity is 10mAh cm -2 The battery underwent continuous charging and discharging cycles for 30 minutes, and the cycle duration before battery failure was recorded. The test results are shown in Table 1. 2) Hydrogen evolution overpotential test method: Use an electrochemical workstation, set the scan rate to 0.01V / s, and the voltage range to -0.6V~0.6V, and plot the Tafel curve; 3) AC impedance spectroscopy test method: Using an electrochemical workstation, the low frequency is set to 0.001 Hz and the high frequency to 1 × 10⁻⁶. 6 Hz; The Zn-Cu half-cells assembled from the electrolytes of Examples 1-6 and Comparative Examples 1-4 were subjected to cycle performance tests: constant current charge-discharge tests were performed using a battery testing system, with the current density set to 1 mA / cm². -2 The capacity is 0.5mAh cm -2 The number of normal cycles before battery failure was recorded, with each cycle consisting of 30 minutes of continuous charging and 30 minutes of continuous discharging. The test results are shown in Table 1. Table 1. Cyclic performance test results of Examples 1-6 and Comparative Examples 1-4
[0068] As shown in Table 1, Examples 1-6 and Comparative Example 1 demonstrate that electrolytes containing appropriate concentrations of amine ligands and reducing metal complexes can effectively extend battery cycle life. Examples 2 and Comparative Examples 2-4 show that, at the same concentration, compared to ethylenediamine and ferrous sulfate existing alone or in simple mixture, the complex form of ethylenediamine ferrous sulfate is more beneficial to battery cycle stability.
[0069] Figures 1-5 Cyclic test diagrams for Zn-Zn symmetrical cells corresponding to Examples 1-4 and Comparative Example 1 of this application are shown respectively. In these diagrams, the time zones with stable voltage fluctuations reflect the normal cycling process. Figures 1-5 As can be seen, the cycle time of Example 1 is 128h, the cycle time of Example 2 is 240h, the cycle time of Example 3 is 210h, the cycle time of Example 4 is 80h, and the cycle time of Comparative Example 1 is only 18h and the voltage curve is always in an unstable fluctuation state. This proves that the complex formed by amine ligands and reducing metals can effectively extend the cycle life of the battery as an electrolyte additive.
[0070] Figure 6 This figure shows the hydrogen evolution overpotential test results for the Zn-Zn symmetrical cells of Examples 1-4 and Comparative Example 1 of this application. In this figure, the horizontal axis represents the electrode potential (Potential / V), and the vertical axis represents the logarithmic current (log(i / A)). The curves in this figure are Tafel curves; under the same current conditions, the greater the potential difference on the corresponding Tafel curve, the higher the hydrogen evolution overpotential. Figure 6 It is evident that the complexes formed by amine ligands and reducing metals at appropriate concentrations help increase the hydrogen evolution overpotential during battery cycling, thereby effectively reducing hydrogen evolution side reactions. Among them, the electrolyte in Example 2 showed the most significant effect in reducing the hydrogen evolution overpotential.
[0071] Figure 7 This is an AC impedance test graph of the Zn-Zn symmetrical battery of Examples 1-4 and Comparative Example 1 of this application. The horizontal axis represents the resistive component of the impedance (Z' / ohm), and the vertical axis represents the reactive component of the impedance (Z'' / ohm). The semicircle diameter of the curve in this graph is a core indicator reflecting the charge transfer resistance. Figure 7 It is evident that the complexes formed by amine ligands and reducing metals can reduce the charge transfer resistance of zinc deposition, thereby improving ion transport efficiency. Among these, the electrolyte in Example 2 exhibits the most significant beneficial effect.
[0072] The test results above show that the electrolyte in Example 2 has a better overall performance in improving battery cycle life. The electrolyte from Example 2 was further assembled into a zinc-iodine (Zn-I2) full battery. The specific assembly method was as follows: High-purity (>99.99%) zinc foil with a thickness of 0.1 mm was stamped into zinc discs with a diameter of 12 mm using a stamping machine. One zinc disc was placed in the negative electrode battery casing, covered with a glass fiber membrane with a diameter of 16 mm, and 100 μL of electrolyte was added. Then, an iodine positive electrode sheet was stacked on top of the electrolyte. Finally, the positive electrode battery casing was covered, and the battery was sealed using a sealing machine to obtain the Zn-I2 full battery. After assembly, a constant current charge-discharge test was performed using a battery testing system, with a current density of 2 A g. -1 The cycle performance of the Zn-I2 full cell was tested. Figure 8 The graph shows the cycle performance test results of the Zn-I2 full cell in Example 2 of this application. The blue curve represents the charge specific capacity, the red curve represents the discharge specific capacity, and the gray curve represents the coulombic efficiency. It can be seen that, compared with the initial level, the charge-discharge specific capacity and coulombic efficiency of the Zn-I2 full cell did not decrease significantly after 10,000 cycles. This indicates that the electrolyte containing 0.004 mol / L ferrous ethylenediamine sulfate in Example 2 can adapt to the long-term cycling of the battery and its function remains stable.
[0073] In summary, the electrolyte provided in this application contains a complex formed by amine ligands and reducing metals, which can effectively suppress hydrogen evolution side reactions, facilitate uniform zinc deposition and improve ion transport efficiency, and have a positive impact on optimizing the long-term stable capacity retention and cycle performance of the battery.
[0074] The above-disclosed embodiments are merely preferred embodiments of this application and should not be construed as limiting the scope of the invention. Those skilled in the art will understand that implementing all or part of the above embodiments and making equivalent changes in accordance with the claims of this invention are still within the scope of this invention.
Claims
1. An electrolyte, characterized in that, It includes zinc salt and electrolyte additives, wherein the electrolyte additives include complexes formed by amine ligands and reducing metal salts, wherein the reducing metal salts are composed of low-valence metal cations and anions, and the reducing metals in the reducing metal salts are less reactive than zinc. The complexes formed by the amine ligands and reducing metal salts include compounds composed of neutral amine ligands, low-valence metal cations, and anions.
2. The electrolyte as described in claim 1, characterized in that, The reducing metals include one or more of chromium, cadmium, iron, cobalt, nickel, molybdenum, tin, lead, copper, mercury, and silver.
3. The electrolyte as described in claim 2, characterized in that, The amine ligands include one or more of methylamine, ethylamine, acetamide, ethylenediamine, propylenediamine, diethylenetriamine, triethylenetetramine, ethanolamine, and ethylenediaminetetraacetic acid.
4. The electrolyte as described in claim 3, characterized in that, The complexes formed by the amine ligands and reducing metal salts include one or more of ferrous ethylenediamine sulfate, ferric triethylenediamine sulfate, cobalt triethylenediamine sulfate, and cobalt ethylenediaminetetraacetic acid sulfate.
5. The electrolyte as described in claim 4, characterized in that, The concentration ratio of the zinc salt to the complex formed by the amine ligand and the reducing metal salt is 1:(0.001-0.004).
6. The electrolyte as described in claim 5, characterized in that, The concentration of the zinc salt is 0.5 mol / L to 3 mol / L.
7. The electrolyte as described in claim 6, characterized in that, The concentration of the complex formed by the amine ligand and the reducing metal salt is 0.0005 mol / L to 0.012 mol / L.
8. The electrolyte as described in claim 7, characterized in that, The complex formed by the zinc salt and the amine ligand with the reducing metal salt contains the same anion.
9. A method for preparing an electrolyte as described in any one of claims 1-8, characterized in that, include: The electrolyte is obtained by mixing the electrolyte additive and zinc salt.
10. An aqueous zinc-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and the electrolyte as described in any one of claims 1-8.
Citation Information
Patent Citations
Complex electrolyte additive for battery, aqueous zinc ion battery electrolyte and aqueous zinc ion battery
CN119852565A